Effect of age of Awassi ewes crossed with Naimi rams on some growth characteristics and litter size - Dalaf Ali Hussein (Universitas Airlangga, 2024)
The study focused on Awassi ewes crossed with Naimi rams. Ewes weight and age were closely related to their productivity, especially on female reproductive performance, therefore this research studied the effect of ewes age to their weight, as well as the effect of the ewes age on the weight of their lambs at birth, at one month, 4 month and to their sex and fertility. In the Awassi ewes used in this study, mature body size was attained at the age of 4 then it started to decline. At lambing, the lambs whose mothers were at the age of 5 years outperformed the rest of the age groups of their mothers, and at one month, the lambs whose mothers were at the age of 3 years outperformed (p ≤0.05) the rest of the age groups of their mothers. The weight of the lambs at weaning (4 months of age) showed the highest in the lambs whose mothers were 3 to 4 years old. The largest number of male lambs were obtained from ewes aged 2.5 and 3 years (75 and 88.9% respectively). Singleton births were 100% for all ewe ages, except for the ewes aged 2.5 and 3 years (40 and 20%, respectively). The highest number of twin births (80%) (p ≤0.05) was obtained in lambs whose mothers were 3 years old, while the highest litter size was 1.8.